PENGARUH PERENDAMAN DAUN KETAPANG TERHADAP PERFORMA PRODUKTIVITAS DAN KUALITAS WARNA IKAN ZEBRA (Danio rario) - Asrullah Akbar Anwar; Risfany Risfany; Dheni Rossarie; Sri Wahyuni Firman (Universitas Mataram, 2026)
Zebra fish (Danio rerio) is a widely cultivated ornamental freshwater species valued for its distinctive body stripes. However, color fading during the rearing period remains a common problem for fish farmers. Ketapang leaves (Terminalia catappa) contain various bioactive compounds, including tannins, flavonoids, and saponins, which are known to improve fish health and potentially enhance pigmentation. This study aimed to determine the effect of ketapang leaf soaking water on the improvement of color quality in Zebra fish (Danio rerio). The research was conducted for 28 days using a Completely Randomized Design (CRD) with five treatments and three replications: A (control/100% freshwater), B (25% ketapang leaf extract), C (50%), D (75%), and E (100%). The observed parameters included survival rate, absolute length growth, absolute weight growth, color quality, and water quality (pH, DO, and temperature). Color quality was assessed using visual color grading and evaluation by 50 panelists. The results indicated that the use of ketapang leaf soaking water significantly influenced the enhancement of color quality in Zebra fish. Treatment D (75% ketapang leaf soaking water) produced the highest color brightness score, both visually and based on panelist assessments. The highest survival rate was recorded in treatment E (100%), while the highest weight growth occurred in treatment A (control). Water quality parameters, including pH, DO, and temperature, remained within optimal ranges for Zebra fish culture throughout the study